ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK CAT NIPPON PAINT - Helmina Br. Ginting (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
The increasing population of the Indonesian people and the economic crisis that occurred also had an impact on the reduction of available job opportunities. Even several large companies in the capital have downsized the number of workers in their companies. This of course will cause a new problem for this country, namely the increase in the number of unemployed. To avoid this kind of thing, many Indonesian people decide to open a business either only for side income or as a main source of income. Various kinds of business fields are developing in Indonesia, such as property business, event organizer business, tour and travel business. Based on the identification of the problems that have been raised, the formulation of the problem can be formulated as follows: Is there a partial effect of Price, Location, and Product Quality on the Purchase Decision of Nippon Paint Paint Products. Is there any effect of Price, Location, and Product Quality Simultaneously on the Purchase Decision of Nippon Paint Paint Products? Which variable dominantly influences the Purchase Decision of Nippon Paint Paint Products. Based on the results of the t-test of Variable X1 (Price), showing Variable X2 (Location) Variable X3 (Product Quality) the value indicates that it has a significant effect on purchasing decisions. The direction of the positive regression coefficient means that it has a partial effect on the purchasing decisions of the people of Siwalanrejo village, Lamongan. Based on the results of the F test (simultaneously) with the value of Fcount > Ftable, the variables Price (X1), Location (X2), and Product Quality (X3) have a simultaneous effect on purchasing decisions of the people of Siwalanrejo Village, Lamongan. The results of the coefficient of determination test can be seen that the coefficient of determination (adjusted R2) obtained is 0.684. This means that 68.4% of customer loyalty can be explained by price, location, and product quality variables, the remaining 32.6% purchasing decisions are influenced by other variables not examined in this study.